2018
DOI: 10.2147/ndt.s147897
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of catatonia treatment

Abstract: ObjectiveTo investigate the evidence-based treatment of catatonia in adults. The secondary aim is to develop a treatment protocol.Materials and methodsA systematic review of published treatment articles (case series, cohort or randomized controlled studies) which examined the effects of particular interventions for catatonia and/or catatonic symptoms in adult populations and used valid outcome measures was performed. The articles for this review were selected by searching the electronic databases of the Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 38 publications
2
111
0
19
Order By: Relevance
“…One plausible explanation for the catatonia’s chronicity in young people with neurodevelopmental disorders may be delayed diagnoses, which might render treatment more difficult. Based on this experience, Pelzer and colleagues recommend that patients with long term symptoms of catatonia be treated expediently with ECT, a recommendation our experience supports 22. At this time, we feel comfortable advising families that whereas we can’t promise recovery will be rapid, experience supports optimism that with standard of care treatments including lorazepam, ECT and possibly dextromethorphan/quinidine a return to baseline or close to baseline functioning is expected.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…One plausible explanation for the catatonia’s chronicity in young people with neurodevelopmental disorders may be delayed diagnoses, which might render treatment more difficult. Based on this experience, Pelzer and colleagues recommend that patients with long term symptoms of catatonia be treated expediently with ECT, a recommendation our experience supports 22. At this time, we feel comfortable advising families that whereas we can’t promise recovery will be rapid, experience supports optimism that with standard of care treatments including lorazepam, ECT and possibly dextromethorphan/quinidine a return to baseline or close to baseline functioning is expected.…”
Section: Discussionmentioning
confidence: 83%
“…The preponderance of reports in DS, Autism and other neurodevelopmental disorders affirms their efficacy in these populations 69,11,14,53,63. A recent Cochrane report of 31 articles revealed lorazepam response rates of 66–100% in Western countries; ECT response rates varied 59–100% 22. Though, excellent response to ECT is generally acknowledged, including endorsement from the American Academy of Child and Adolescent Psychiatry, rigorous evidence including random controlled trials and meta-analyses have not been performed 6265.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Benzodiazepines are the mainstay of treatment in catatonia. [ 8 ] Furthermore, response to benzodiazepines validates the diagnosis of catatonia [ 9 ]. Some clinicians use the lorazepam challenge test in which 1–2 mg of lorazepam is infused, and the patient is reevaluated for improvement [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…First-generation antipsychotics (FGAs) exhibit a higher potency on the dopamine d2 receptors, potentially increasing the risk for NMS and EPS, and so second-generation antipsychotics (SGAs) are preferred [ 2 ]. Pelzer et al conducted a systematic review of catatonia treatment and found that clozapine outperformed other SGAs by demonstrating an 85% positive response [ 11 ]. In catatonia caused by clozapine withdrawal, clozapine is the first-line treatment.…”
Section: Discussionmentioning
confidence: 99%